THE DETERMINATION OF PERIODS AND THE DEFINITION OF VARIABILITY TYPE OF NEW VARIABLE STAR IRAS 17583+5150 - Solonovich, A. P.; Bryukhanov, I. S. (Одеські астрономічні публікації, 2017)
The measurements of brightness of the star IRAS 17583+5150 discovered using the Odessa observatory negatives are discussed in the article. The proposed types of these stars are IRAS 17583+5150 – type SRB (SRC).